TOURIST PERCEPTION OF TOURIST ATTRACTION IN SOUTHWEST PAPUA - Howay, Musa Seblom; Oraple, Ezri Trifena; Nurteteng, Nurteteng; Nursalim, Nursalim (Universitas Muhammadiyah Makassar, 2025)
This study analyzes tourists' perceptions, satisfaction, and expectations of Southwest Papua's tourist attractions to provide recommendations for improving tourism quality. This study uses qualitative methods, including in-depth interviews, participatory observation, and documentation through video and photos, to explore tourists' perceptions, satisfaction, and expectations in Southwest Papua. The results of this study are: 1) In the three domains of tourists' perceptions, destination attractions, facilities and services, as well as safety and comfort. Some tourists generally expressed positive perceptions, appreciating the authenticity of the natural environment and the immersive cultural experiences. However, certain challenges, such as unpredictable weather, accommodations, homestays, and management issues, led to negative perceptions, particularly among tourists from Asia. 2) Emotional and social satisfaction are the highest-rated aspects experienced by nearly all 350 tourists, surpassing functional satisfaction. Their sense of happiness is attributed to effective tour organization, fluent communication by tour leaders, and well-established social interactions with local communities. 3) Tourists expect better facilities and more government involvement in infrastructure and local training to improve the tourism experience. Collaboration between the government and tourist villages will greatly contribute to enhancing the positive values for visiting tourists.